The Crisis-Resilience of Services Trade - Borchert, I. (2012)
Much attention has been focused on the impact of the current crisis on goods trade; hardly any on its impact on services trade. Using new trade data from the USA, and more aggregate data from other OECD countries, the authors show that services trade is weathering the current crisis much better than goods trade. On the basis of new evidence from Indian services exporters, it is suggested that services trade is more robust relative to goods trade for three reasons: less cyclical demand; lesser dependence on external finance; and few explicitly protectionist measures so far taken in services.